Analisis Tugas dalam Buku Tematik Siswa Muatan Pembelajaran IPA Kelas VI Berdasarkan Unsur Pengetahuan, Konteks, dan Proses Sains - Tri Lestari; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar (Kapedas), 2023)
This study aims to describe the elements of knowledge, context and science processes in the assignments in the 2013 Curriculum 2013 students' thematic books Themes 1 to 5 content of Science class VI Elementary School. This type of research is descriptive research. The object of this research is the elements of knowledge, context, and science process which are analyzed for their appearance in the 2013 Curriculum 2013 students' thematic books Themes 1 to 5 content of Class VI Elementary Science Science lessons. The research instrument is an analysis sheet of elements of knowledge, context and science processes. The data analysis technique used is descriptive. Appearance percentage category uses rater agreement percentage formula. The results showed that: 1) Elements of knowledge in the thematic books of science content for Class IV, namely indicators presenting concepts with an average percentage of 54.24% with percentage details in theme 1 of 50%, theme 2 of 50%, theme 3 of 54.55% , theme 4 of 50%, and theme 5 of 66.67%. (2) 18 appearances of the context elements of Theme 4 with the most indicators namely issues concerning natural resources 6 times (33.33%), issues concerning the environment 4 times (22.22%), issues about danger 2 times with a percentage of 11.11%, and indicators of issues regarding the boundaries of science and technology 6 times (33.33%). (3) Process elements in Theme 2 are 23 occurrences (76.67%), Theme 1 are 22 occurrences (73.33%), Theme 5 are 21 occurrences (70%), Theme 3 are 18 occurrences (60%), and Theme 4 with 17 occurrences (56.67%).